Compulsory resignation regime for members of the Territorial Assembly of French Polynesia - decision of 11 June 1993 of the Administrative Tribunal of Papeete - Sage, Yves-Louis; Moyrand, A (Victoria University of Wellington Law Review, 1996)
This article is a case note of a decision from the Administrative Tribunal of Papeete, French Polynesia. Although no constitutional provision speaks of it expressly in the context of the legislative regime of the Overseas Territories, the principle is that legislative speciality governs the application of metropolitan laws in the Territories. In 1992, however, the Territory of French Polynesia experienced a somewhat confused institutional situation: the fortunes of political alliances led Mr Vernaudon, member and President of the Territorial Assembly, and who was angered by the association of Mr Flosse (his former political ally) with Mr Juventin (his former rival) to make use of powers inherent in his position as President to refuse to call the Assembly to meeting. This article discusses two main issues stemming from these events: procedural guarantees (i.e. a failure to respect a member’s rights), and constitutional reforms (i.e. whether the compulsory resignation principle is appropriate in French Polynesia). The author concludes that the compulsory resignation process should be repealed, as it seems particularly offensive to confer on a majority of a political assembly the power to dismiss any political opponent so easily.